Effect of gamma irradiation on the bulk –etch rates of lexan polycarbonate solid state nuclear track detector. (Journal of the College of Basic Education, 2023)
In the present work, we have determined the bulk-etch rates of lexan polycarbonate (C16H14O3)n nuclear track detector at different temperatures to deduce its activation energy, the effects of gamma irradiation on this detector in the dose range of 23 – 71.3 kGy have been studied by using the etching technique. The bulks etch rates increase and the activation energies for bulk etching decrease with the increase in gamma dose. These results have been explained on the basis of chain scission of the detector due to gamma irradiation.